Lamb mortality due to bronchopneumonia secondary to orf infection and control by vaccination - GIADINIS (Ν.Δ. ΓΙΑΔΙΝΗΣ), N. D.; ARSENOPOULOS (Κ. ΑΡΣΕΝΟΠΟΥΛΟΣ), K.; KRITSEPI-KONSTANTINOU (Μ. ΚΡΙΤΣΕΠΗ-ΚΩΝΣΤΑΝΤΙΝΟΥ), M.; TSAKOS (Π. ΤΣΑΚΟΣ), P.; ILIADOU (Π. ΗΛΙΑΔΟΥ), P.; MANGANA-VOUGIOUKA (ΜΑΓΚΑΝΑ-ΒΟΥΓΙΟΥΚΑ), O.; ABD EL-TAWAB, M. M. (Journal of the Hellenic Veterinary Medical Society, 2018)
Newborn lambs of a sheep flock in Greece showed clinical signs of bronchopneumonia with high perinatal mortality. All different therapeutic protocols that were applied were ineffective. Clinical examination of 4 lambs confirmed that the animals exposed signs of bronchopneumonia and contagious ecthyma. Haematological parameters of all the 4 lambs were within normal limits, while gross pathologic findings were compatible with bronchopneumonia. Lung and scab specimens were taken from all 4 animals for microbiological examination. Orf virus was isolated from all scab specimens, while lung specimens were found negative. In contrast, all lung specimens yielded colonies of Pasteurella multocida, Manheimia haemolytica and Mycoplasma spp. All the remaining pregnant ewes of the flock were vaccinated against orf virus with a commercial live attenuated vaccine. It resulted in diminishment of bronchopneumonia cases in the newborn lambs. In conclusion, it is supported that the lambs in the present flock were immune-suppressed due to orf infection and therefore exposed secondary bronchopneumonia.